Sex reversal of red tilapia using 17α-methyltestosterone-enriched feed and increased temperature - Ayuningtyas, Safira Qisthina; Junior, Muhammad Zairin; Soelistyowati, Dinar Tri (Jurnal Akuakultur Indonesia, 2015)
ABSTRACT The growth rate between male and female red tilapia Oreochromis sp. is different. Generally, the male red tilapia grows faster than the female. Furthermore, the maturation process of red tilapia is relatively fast which causes slower growth rate. One of solutions to this problem is by rearing all male population or mono-sex culture. The method used in this study was commercial feed enrichment with 17α-methyltestosterone at different dosages and water temperature manipulation. The purpose of this research was to examine the effects of commercial feed enrichment with different dosages of 17α-methyltestosterone and water temperature manipulation on success rate of sex reversal of red tilapia into all male population. This research consisted of different temperature treatments (with and without water heating) and 17α- methyltestosterone dosages (0, 10, 20 mg/kg of commercial feed). The best dosage of 17α-methyltestosterone was 20 mg/kg of commercial feed with male to female sex ratio of 86.31%, daily growth rate of 8.18%, and feed conversion ratio of 1.53. In this study, the best treatment to produce the male seeds was the 17α-methyltestosterone treatment. Keywords: 17α-methyltestosterone, sex reversal, red tilapia, temperature  ABSTRAK Ikan nila merah Oreochromis sp. memiliki laju pertumbuhan yang berbeda antara ikan jantan dan betina. Umumnya ikan nila merah jantan lebih cepat tumbuh dibandingkan betinanya. Selain itu, ikan nila memiliki sifat cepat matang gonad dan mudah memijah sehingga akan menghambat pertumbuhan ikan. Salah satu cara untuk mengurangi masalah yang terjadi yakni dengan memelihara populasi ikan nila merah tunggal kelamin atau monoseks jantan. Metode yang dilakukan adalah pemberian hormon 17α-metiltestosteron dengan dosis berbeda melalui pakan buatan dan peningkatan suhu air. Penelitian ini bertujuan untuk mengetahui pengaruh dosis hormon 17α-metiltestosteron melalui pakan buatan dan peningkatan suhu air terhadap keberhasilan alih kelamin jantan pada ikan nila merah. Penelitian ini terdiri atas perlakuan suhu (dengan dan tanpa pemanasan air) dan dosis 17α-metiltestosteron (0, 10, 20 mg/kg pakan). Dosis hormon 17α-metiltestosteron terbaik yang didapatkan adalah 20 mg/kg pakan dengan nisbah kelamin jantan 86,31%, laju pertumbuhan harian 8,18%, dan rasio konversi pakan 1,53. Pada penelitian ini perlakuan terbaik untuk menghasilkan benih jantan adalah perlakuan dosis 17α-metiltestosteron. Kata kunci: 17α-metiltestosteron, alih kelamin, ikan nila merah, suhu